List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. (Policy Papers; Policy Paper ;, 2017)
In line with a framework introduced in 2012 for addressing excessive delays in the completion of Article IV consultations, this report lists the IMF members for which the Article IV consultation has been delayed by more than 18 months at end-May, 2017. The delay is counted past the stipulated date for the consultation plus any applicable grace period. There are no countries for which the mandatory financial stability assessments are delayed by more than 18 months at end-May, 2017.